P120 The impact of advance care planning of place of death, a hospice retrospective cohort study. (1st October 2013) - Rich, Alison; Julian, Abel; Bailey, John
Abstract : Objectives: There is limited evidence of the impact of advance care planning (ACP) on outcomes. We conducted a retrospective cohort study on deaths of all patients known to a hospice in a 2.5-year period to see if use of ACP affected actual place of death, hospital use and cost of hospital care in the last year. Results: 969 patients were included. 550 (57%) people completed ACP. 414 (75%) achieved their choice of place of death. For those who chose home, 34 (11.3%) died in hospital; a care home 2 (1.7%) died in hospital; a hospice 14 (11.2%) died in hospital and 6 (86%) who chose to die in hospital did so. 112 (26.5%) of people without ACP died in hospital. Mean number of days in hospital in the last year of life was 18.1 in the ACP group and 26.5 in the non-ACP group (p < 0.001). Mean cost of hospital treatment during the last year of life for those who died in hospital was £11, 299, those dying outside of hospital £7, 730 (p < 0.001). Mean number of emergency admissions for those who died in hospital was 2.2 and who died elsewhere was 1.7 (p < 0.001). Conclusions: ACP can be used routinely in a hospice setting. Those who used ACP spent less time in hospital in their last year. ACP is associated with a reduction in the number of days in hospital in the last year of life with less hospital costs, supporting the assumptions made in the End of Life Care Strategy 2008.